Analysis of Outpatient Waiting Time Determinants in Hospitals Based on the Donabedian Framework - Rika Maretha; Haerawati Idris; Rizma Adlia Syakurah (Indonesian Journal of Global Health Research, 2025)
Waiting time is one of the indicators in evaluating the quality of outpatient services in hospitals. Long waiting times are often the main complaint of patients and have the potential to reduce satisfaction and effectiveness of services. This article aims to review the available literature on patient waiting times and identify factors that contribute to waiting times for outpatient services. The method used is a Systematic Literature Review using the Preferred Reporting Items for Systematic Reviews (PRISMA) flow by collecting articles from the Google Scholar and PubMed databases published between 2019 and 2024 with the keywords " outpatient", "waiting time" and "hospital", as well as in Indonesian: "waktu tunggu, perawatan jalan" and "poliklinik". Based on the analysis results, 20 articles were selected from the 130 articles selected that met the inclusion criteria and were subsequently analysed and classified using the Donabedian theoretical framework, which consists of three components: structure, process, and outcome. The analysis results indicate that structural factors, such as limited medical personnel, inadequate infrastructure, and inefficient queuing systems, are the primary causes. In the process aspect, doctor delays, lengthy administrative processes, and a lack of service system integration also contribute to lengthening waiting times. Meanwhile, outcome factors are closely related to patient perceptions and satisfaction levels. The study's conclusions suggest that improving outpatient wait times necessitates a comprehensive approach that encompasses enhancing service structure, process efficiency, and prioritising patient outcomes.